ANALISIS RISIKO PRODUKSI USAHA TERNAK SAPI PERAH PADA KELOMPOK TANI TERNAK DI KECAMATAN GETASAN SEMARANG - Berlian Syahrial Firdaus Al Farizqie; Wiludjeng Roessali; Suryani Nurfadillah (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
The growth of milk consumption in Indonesia amounted to 5.09% is still higher compared with production with 3,17%. The low production is caused by not optimal in milk production with an average of 8,82 litres/head/day, in addition there are fluctuations in production. These fluctuations mark the presence of production risk, make a new issue for the dairy cows development. The production risk becomes important to be studied in order to improve the productivity and development of dairy cattle business. The purpose of this study is to analyze the level of risk and the risk agents as well as a mitigation strategy to handle it. This research was conducted in the month of March 2020 in the Getasan District because it is one of the dairy centers in the Semarang Regency. The determination of the location of the Dairy Cattle Farmers Association (DCFA) is determined purposively taken the Rias DCFA in the Kopeng Village with consideration to have a suitable location for the cultivation of dairy cows and is the group with the number of cattle is highest in the Kopeng Village. The determination of the sample using the census method by the respondents as many as 34 people. The primary data obtained through interviews farmers based on questionnaires and direct observation. The secondary data obtained through the study note that there is at the Rias DCFA and relevant literature. Data analysis using quantitative calculation value of the Coefficient of Variation (KV) and House of Risk (HOR) method. The results showed that the level of production risk as very high and experienced the extreme fluctuations with the KV value of 22.39%. Based on the HOR phase 1 there are 9 risk agent the main cause of the risk events that become priority to be addressed. The results of the HOR phase 2 achieved 3 mitigation strategy priority to be applied to handle 9 of these risk agents.